School food advice and its performance within the family farming and national school food program in piauiens territories (Research, Society and Development, 2020)
This study aims to analyze the performance of the School Meals Council, such as social control in the context of family farming and the National School Meals Program in municipalities in Piauí. This is a cross-sectional study, involving 41 municipalities in the middle north portion of the state of Piauí. Information was collected on the relationship with the municipal management and knowledge of the performance of the School Food Councils on the regulations regarding the Program. The members of the School Meals Councils of the municipalities studied claimed to know their duties, to be in a regular situation, to have the structure to develop their activities and frequency of meetings, to know the resources directed to school meals, to monitor the purchase and elaboration of menus and have access to information on the purchase of family farming products. The importance of periodic training is emphasized in order to update the full knowledge of the directors regarding the broad attributions foreseen for them to exercise the social control of the program, guaranteeing working conditions so that they can carry out their activities as planned. The importance of periodic training is emphasized in order to update the knowledge of the counselors regarding the duties provided for the exercise of social control of the program, as well as the guarantee of working conditions so that they can exercise their activities as planned.